1973
DOI: 10.1017/s002185960005704x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of wheat genotypes with a specific factor of the environment

Abstract: SummarySeveral alternative statistical approaches to the analysis of genotype-environment interactions are summarized, and their inter-relationships are presented mathematically and graphically. An experiment was designed to test the ability of these analyses to satisfactorily describe genotype-environment interactions and to locate genotypes causing or contributing significantly to such interactions in a situation where environments differed in only one factor, i.e. soil nitrogen status.Twenty-five lines of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

1973
1973
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…Segundo Eberhart & Russell (1966), a cultivar ideal é aquela que tem produção média alta, coeficiente de regressão igual à unidade e desvio de regressão pequeno, isto é, aquele desvio que tem resposta positiva à melhoria das condições ambientais (b 1 = 1,0), e comportamento altamente previsível (s 2 d i = 0,0). Easton & Clements (1973) e Lin et al (1986 salientaram que a caracterização da adaptabilidade e estabilidade fenotípica é relativa ao conjunto dos genótipos incluídos no experimento. Como a produtividade do ambiente é expressa pelo próprio desempenho médio dos genótipos no experimento, não há qualquer segurança de que um genótipo manterá o mesmo comportamento quando avaliado com diferentes genótipos.…”
Section: Introductionunclassified
“…Segundo Eberhart & Russell (1966), a cultivar ideal é aquela que tem produção média alta, coeficiente de regressão igual à unidade e desvio de regressão pequeno, isto é, aquele desvio que tem resposta positiva à melhoria das condições ambientais (b 1 = 1,0), e comportamento altamente previsível (s 2 d i = 0,0). Easton & Clements (1973) e Lin et al (1986 salientaram que a caracterização da adaptabilidade e estabilidade fenotípica é relativa ao conjunto dos genótipos incluídos no experimento. Como a produtividade do ambiente é expressa pelo próprio desempenho médio dos genótipos no experimento, não há qualquer segurança de que um genótipo manterá o mesmo comportamento quando avaliado com diferentes genótipos.…”
Section: Introductionunclassified
“…For inheritance studies they should therefore be considered in combination and the techniques of Thomas et al (1971) may be suitable. Easton and Clements (1973) emphasise the importance of examining individual genotypes and this applies especially to vegetatively propagated crops. Marmion and Montrose illustrate their point.…”
Section: Results (I) Plant Sizementioning
confidence: 99%
“…In such cases some plant breeders and agronomists have then found the concept of two stability parameters useful. However, Easton and Clements (1973) compared various methods for assessing stability and found them to be only moderately good at identifying genotypes with atypical behaviour; by choosing a subset of genotypes it was possible to make a previously stable genotype appear unstable. Similarly, found that the selection of a subset of environments changed the relation between mean performance and both linear and non-linear components of stability.…”
Section: The Interpretation Of Ge Interactions and The U5e Made Of Thmentioning
confidence: 99%